2020
DOI: 10.1111/jnc.14949
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of iPS‐derived vascular endothelial cells improves white matter ischemic damage

Abstract: White matter infarct induces demyelination and brain dysfunction. We previously reported that transplantation of brain microvascular endothelial cells improved the behavioral outcome and promoted remyelination by increasing the number of oligodendrocyte precursor cells in the rat model of white matter infarct. In this study, we investigated the effects of transplantation of vascular endothelial cells generated from human induced pluripotent stem cells (iPSCs) on the rat model of white matter infarct. Seven day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 37 publications
2
11
0
Order By: Relevance
“…Research into regenerative medicine, in which stem cells including induced pluripotent stem (iPS) cells and embryonic stem (ES) cells are transplanted, is drawing attention as a new treatment for central nervous system diseases such as cerebral infarction and spinal cord injury. 12 , 13 However, there are many problems with stem cell transplantation, such as hazardous immune rejection against allografts and potential oncogenetic risk as well as complicating process of preservation and culture methods of iPS/ES cells. 14 , 15 , 16 Recently, various studies have demonstrated that culture supernatants of stem cells possess ability of repairing damaged tissues, protect tissues, and ultimately regenerate organs with utilizing their own stem cells in situ .…”
Section: Discussionmentioning
confidence: 99%
“…Research into regenerative medicine, in which stem cells including induced pluripotent stem (iPS) cells and embryonic stem (ES) cells are transplanted, is drawing attention as a new treatment for central nervous system diseases such as cerebral infarction and spinal cord injury. 12 , 13 However, there are many problems with stem cell transplantation, such as hazardous immune rejection against allografts and potential oncogenetic risk as well as complicating process of preservation and culture methods of iPS/ES cells. 14 , 15 , 16 Recently, various studies have demonstrated that culture supernatants of stem cells possess ability of repairing damaged tissues, protect tissues, and ultimately regenerate organs with utilizing their own stem cells in situ .…”
Section: Discussionmentioning
confidence: 99%
“…iVEC differentiation from human iPSCs was performed according to previously described [ 11 ]. Briefly, iPSCs were singularized with Accutase (Millipore, Cat# SCR005) and seeded on growth factor-reduced Matrigel-coated 6-well plate at a density of 10,000 cells/cm 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Our previous reports showed transplantation of rat brain microvascular endothelial cells and human induced pluripotent stem cell (iPSC)-derived vascular endothelial cells (iVECs) improves locomotor deficit, reduces infarct area, promotes remyelination, and suppresses neuroinflammation [ 10 , 11 ]. We also showed that transplantation of vascular endothelial cells into the infarct area promotes increase of oligodendrocyte precursor cells (OPCs) in the region [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The tight dependence of WM on the vascular system requires that reparative therapies integrate a multifactorial approach that counters endothelial dysfunction and inflammation, since oligodendrogenesis may not be sufficient to fully restore WM fibers (Hamanaka et al, 2018). Indeed, transplantation of hiPSC-derived endothelial cells (ECs) within demyelinated areas has been shown to form functional vessels in a mouse model of WM ischemic infarct (Xu et al, 2019). Transplantation of ECs enhanced cell survival, increased the number of OPCs, suppressed inflammatory responses and astrocytosis, decreased the ischemic area, promoted remyelination, and recovered limb coordination.…”
Section: Molecular Basis Of Tbi-induced Neuronal Dysfunction and Repamentioning
confidence: 99%